Capecitabine plus oxaliplatin versus gemcitabine plus oxaliplatin as first-line therapy for advanced biliary tract cancers: a multicenter, open-label, randomized, phase III, noninferiority trial. (20th February 2019) - Kim, S T; Kang, J H; Lee, J; Lee, H W; Oh, S Y; Jang, J S; Lee, M A; Sohn, B S; Yoon, S Y; Choi, H J; Hong, J H; Kim, M -J; et al.
Abstract: Background: Capecitabine plus oxaliplatin (XELOX) has shown modest activity and tolerable toxicity in a phase II trial for biliary tract cancers (BTCs). Meanwhile, gemcitabine plus oxaliplatin (GEMOX) has been the reference arm in recent phase II and III trials for BTCs. We aimed to investigate the efficacy of XELOX versus GEMOX as first-line therapy for advanced BCTs. Patients and methods: In this open-label, randomized, phase III, noninferiority trial, we randomly selected patients with metastatic BCTs to receive GEMOX (gemcitabine 1000 mg/m 2 on days 1 and 8, and oxaliplatin 100 mg/m 2 on day 1) or XELOX (capecitabine 1000 mg/m 2, twice daily, on days 1–14 and oxaliplatin 130 mg/m 2 on day 1) as first-line treatment, given every 3 weeks, totaling eight cycles. The primary end point was to prove the noninferiority of XELOX to GEMOX in terms of 6-month progression-free survival (PFS) rate. Results: In total, 114 patients randomly received GEMOX and 108 randomly received XELOX. The median PFS was 5.3 months for the GEMOX group and 5.8 months for the XELOX group. The 6-month PFS rate was 44.5% for the GEMOX group and 46.7% for the XELOX group. The 95% confidence interval of the 6-month PFS rate difference between both groups was −12% to 16%, meeting the criteria for noninferiority of XELOX to GEMOX. There was no difference in objective response ( P =0.171) and median overall survival ( P =0.131) between both groups. The most common grade three to four adverse events were neutropenia and thrombocytopenia. No patient died of treatment-related causes. The XELOX group had significantly lower frequencies of hospital visits than the GEMOX group ( P <0.001). Conclusion: XELOX showed significant noninferiority to GEMOX in terms of 6-month PFS rate. Thus, XELOX could be an alternative first-line treatment of BCTs. Trial Registration: This study was registered in ClinicalTrials.gov (number NCT01470443).